2020
DOI: 10.1093/ndt/gfaa142.p1035
|View full text |Cite
|
Sign up to set email alerts
|

P1035urinary Heme Oxygenase 1 as a Marker for Early Diagnosis of Diabetic Nephropathy

Abstract: Background and Aims Heme oxygenase 1 is an essential enzyme in heme catabolism induced by oxidative stress.It induced in avariety of kidney substructres in response to injury, including proximal tubules, glomeruli and renal interstitium.We aimed to assess the possible role of heme Oxygenase-1 as a potential marker in early diagnosis of diabetic nephropathy. Method This case control study was conducted in Ain Shams university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The biplot showed that almost all the variables and genotypes gave a high degree of variation. Previous studies enunciated that various crop genotypes revealed greater variation for most yield-related traits (Ravi et al, 2018;Worknesh et al, 2019;Ahmed et al, 2020). 13,5,18,1,12,33,11,2,26,9,17,26,38,37,20,39,3* 28,29,18,30,31,33,27,20,32,21,26,3* Quadrate II 11,30,44,6,21,15,22,35,36* 22,24,23,27,44,35,12,13,17,42,41* Quadrate III 23,34,31,28,25,40,32,19,24,45,47,…”
Section: Principal Component Analysismentioning
confidence: 99%
“…The biplot showed that almost all the variables and genotypes gave a high degree of variation. Previous studies enunciated that various crop genotypes revealed greater variation for most yield-related traits (Ravi et al, 2018;Worknesh et al, 2019;Ahmed et al, 2020). 13,5,18,1,12,33,11,2,26,9,17,26,38,37,20,39,3* 28,29,18,30,31,33,27,20,32,21,26,3* Quadrate II 11,30,44,6,21,15,22,35,36* 22,24,23,27,44,35,12,13,17,42,41* Quadrate III 23,34,31,28,25,40,32,19,24,45,47,…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Inhibition of HO-1 by HO-1 inhibitors such as ZnPP showed an increase in the number of apoptotic cells, which also indicated the protective effect of HO-1. Ahmed et al., using Streptozotocin-induced diabetes as a model in spontaneously hypertensive rats (SHR), found that glomerular albumin permeability was higher and apoptosis was increased in diabetic SHR compared with the control group ( 48 ). After induction of HO-1 overexpression by COPP, the permeability of albumin and apoptosis decreased.…”
Section: Study On the Relationship Between Ho-1 And Kidney Diseasesmentioning
confidence: 99%
“…The protective role of HO-1 in DKD has also been demonstrated in relevant clinical studies. One study found that HO-1 can be used as an early biomarker of DKD ( 48 ). Urinary HO-1 levels were significantly higher in the diabetic nephropathy group than in the non-diabetic nephropathy group, and the increase in urinary HO-1 levels in these patients preceded significant proteinuria.…”
Section: Study On the Relationship Between Ho-1 And Kidney Diseasesmentioning
confidence: 99%
See 1 more Smart Citation